Motor Imagery Training of Reaching-to-Grasp Movement Supplemented by a Virtual Environment in an Individual With Congenital Bilateral Transverse Upper-Limb Deficiency - Mencel, Joanna; Jaskólska, Anna; Marusiak, Jarosław; Kamiński, Łukasz; Kurzyński, Marek; Wołczowski, Andrzej; Jaskólski, Artur; Kisiel-Sajewicz, Katarzyna (Frontiers in Psychology, 2021)
This study explored the effect of kinesthetic motor imagery training of reaching-to-grasp movement supplemented by a virtual environment in patient with congenital bilateral transverse upper-limb deficiency, based on a theoretical assumption, that it is possible to conduct such training in a patient. The aims of the study were to evaluate whether cortical activity related to motor imagery of reaching (MIR) and motor imagery of grasping (MIG) of the right upper limb was changed by computer-aided imagery training (CAIT) in patient that was born without upper limbs and a healthy control subject, as characterized by multi-channel EEG signals recorded before and after 4, 8 and 12 weeks of CAIT. The main task during CAIT was to imagine kinesthetically the execution of reaching-to-grasp movements without any muscle activation that was supplemented by computer visualization of movements provided by a special headset. Our experiment has shown that CAIT can be conducted in patient with higher vividness of imagery for reaching than grasping task. Our results confirm that CAIT can change brain activation patterns in areas related to the motor planning and execution of reaching and grasping movements, and that the effect was more pronounced in the patient than in the healthy control subject. The results show that CAIT has a different effect on the cortical activity related to the motor imagery of a reaching task than on the cortical activity related to the motor imagery of a grasping tasks. The change observed in activation patterns could indicate CAIT-induced neuroplasticity, which could potentially be useful in rehabilitation or for brain-computer interface purposes for such patients, especially before and after transplantation. This study is a part of registered experiment (ID: NCT04048083).